Identification of an APC Variant in a Patient with Clinical Attenuated Familial Adenomatous Polyposis - Andrew T. Schlussel; Susan S. Donlon; Faye A. Eggerding; Ronald A. Gagliano (Case Reports in Medicine)
Introduction. The objective of this case report is to discuss an unclassified germline variant of the adenomatous polyposis coli (APC) gene identified in an older patient with attenuated familial adenomatous polyposis syndrome (AFAP). Methods. We present a case report of a 66-year-old man diagnosed with AFAP. Colonoscopy found multiple polyps and invasive adenocarcinoma arising in the transverse colon. Samples were tested for mutations in the APC gene. Results. DNA sequencing of germline DNA identified a cytosine (C) to thymine (T) transition at nucleotide 1240, heterozygous. The C to T transition at codon 414 is predicted to convert an arginine residue to a cysteine that is possibly pathogenic. Analysis of the patient’s colon tumor DNA indicated that the tumor had lost the mutant variant allele and retained only the normal allele, suggesting that the variant may not be significant. Conclusions. The p.R414C variant has been described previously as a germline mutation of probable pathogenicity. This substitution should be considered an unclassified variant and possibly not pathogenic. These findings support the need for further genetic testing of tissue, as well as for developing a mechanism for testing all variants, as this could significantly impact the lives of patients and their family members.